Anatomic and Visual Outcomes Following Surgical Repair of Retinoschisis-Related Retinal Detachments. (January 2019) - Stem, Maxwell S.; Garretson, Bruce R.; Todorich, Bozho; Price, Jade; Weiner, Adam J.; Randhawa, Sandeep; Drenser, Kimberly A.; Capone, Antonio; Hassan, Tarek S.; Ruby, Alan J.; Williams, George A.; Wolfe, Jeremy D.; et al.
Purpose: The purpose of this article is to report the characteristics of patients with retinoschisis-related retinal detachments and to summarize their clinical outcomes after surgical repair. Methods: A single-center interventional case series of 37 eyes from 35 patients who underwent surgery to repair a retinoschisis-related retinal detachment between January 1, 2009 and January 1, 2017 was conducted. Results: The mean ± SD age at the time of the first retinal detachment repair was 63 ± 13 years. As the initial surgery, scleral buckle was performed in 14 eyes, scleral buckle + vitrectomy in 14 eyes, and vitrectomy in 9 eyes. The single-operation success rate for the entire cohort was 65% (24/37), and the final anatomic success rate was 97% (36/37). Among eyes requiring more than 1 surgery, 46% (6/13) developed proliferative vitreoretinopathy. Best-corrected visual acuity improved or remained stable after 1 year of follow-up in the majority (n = 27, 73%) of eyes. The mean (SD) number of surgeries required to achieve the final anatomic and visual result was 1.8 (1.2) for all eyes (range, 1-5 surgeries). Conclusion: The single-surgery success rate for retinoschisis-related retinal detachments was lower than that reported for typical rhegmatogenous retinal detachments, and the incidence of proliferative vitreoretinopathy was higher. When counseling patients with retinoschisis-related retinal detachments, it is important to caution them that they may require more than 1 surgery to achieve anatomic success.